From trickle down to inclusiveness :: do participatory planning and budgeting processes matter for the formulation of policy? (Bangladesh Journal of Public Administration, 2021)
Inclusiveness of the excluded is a new phenomenon in the study of governance. This is suggested in the researches that macroeconomic aggregates do not, as had been assumed, have a ‘trickle-down effect. The actors including state and societal that either play a dominant role or do not play any role at all in the policy process become evident in the systematic study of the policy formulation process. In Bangladesh, the participatory policy formulation process is introduced by the Local Government (Union Parishad) Act, 2009. This study used a qualitative case-study methodology, backed by secondary documentary analysis, and assessed the process of formulation of the policy at the participatory planning and budgeting processes at the local level in six Union Parishads(UP), the lowest administrative tier of Bangladesh. Based on empirical data this paper found that citizens were able to identify their priority needs of life if they were offered the opportunity.The nexus between donors and government works as an iron triangle and as an outcome, the citizens become unwilling to participate in those processes when they are being perceived that their needs are being neglected due to resource constraints. The absence of societal actors to play a dominant role to act as a pressure group in the policy formulation process, resource constraints, and patron-client relationship are some factors that exclude the demands of the grass-root level citizens. It is suggested that governments need to explicitly consider the human development objectives of local people when formulating macroeconomic policy.